2007
DOI: 10.1177/0363546507308360
|View full text |Cite
|
Sign up to set email alerts
|

Double-Bundle Anterior Cruciate Ligament Reconstruction Using Hamstring Autografts and Bioabsorbable Interference Screw Fixation

Abstract: Rotational stability of the knee is better when using the double-bundle technique instead of the single-bundle technique in anterior cruciate ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
171
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(191 citation statements)
references
References 33 publications
7
171
1
5
Order By: Relevance
“…28 Nine studies with a total of 335 patients which included Lysholm score were available for comparison. 6,18,[28][29][30][31][32][33][34] Similarly subjective IKDC score was reported in seven studies with 256 patients. IKDC score in our study was found to be comparable to that in other studies.…”
Section: Discussionmentioning
confidence: 89%
“…28 Nine studies with a total of 335 patients which included Lysholm score were available for comparison. 6,18,[28][29][30][31][32][33][34] Similarly subjective IKDC score was reported in seven studies with 256 patients. IKDC score in our study was found to be comparable to that in other studies.…”
Section: Discussionmentioning
confidence: 89%
“…[11][12][13][14][15][16] On the other hand, only a clinical report 17 has introduced a remnant-preserving technique for double-bundle ACL reconstruction, in which 2 femoral tunnels and one tibial tunnel were made, although anatomic double bundle ACL reconstruction procedures have recently attracted notice because of biomechanical advantages in laboratory studies. [18][19][20][21][22][23][24][25][26][27][28] However, no previous studies have shown clinical evidence about utility of the ACL remnant tissue preservation in ACL reconstruction as of yet. To verify whether preservation of the ACL remnant tissue can really improve proprioceptive functions and enhance revascularization, we should conduct a randomized comparative trial with a sufficient number of patients to compare the 2 ACL reconstruction procedures with and without the remnant preservation in terms of proprioception and revascularization of the graft.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the femoral side tunnels were made using the free-hand technique through an anteromedial portal. Järvelä et al [37] reported longer follow-up (24-35 months) results in 2008. The study design included an SB group with metallic screws (N025), an SB group with bioabsorbable screws (N027) and a DB group with bioabsorbable screws (N025).…”
Section: Randomised Controlled Studiesmentioning
confidence: 99%